The effects of high volume nano palm oil fuel ash on microstructure properties and hydration temperature of mortar. (15th September 2015) - Lim, Nor Hasanah Abdul Shukor; Ismail, Mohamed A.; Lee, Han Seung; Hussin, Mohd Warid; Sam, Abdul Rahman Mohd.; Samadi, Mostafa
Highlights: High volume of nano POFA as cement replacement improves strength. Nano POFA reduces hydration temperature of massive concreting in early age. Treatment of POFA increases pozzolanic properties and activity index. Abstract: The effect of high volume nano palm oil fuel ash in the mortar was investigated. This study covers basic properties like the morphology of the composite, the hydration temperature, strength activity index, thermal conductivity and microstructure properties with regards to the variations in the mix design process of mortar. The effects of fineness of the ash on the strength properties of mortar were also investigated. To get a better performance in terms of strength development, the ash used has gone through heat treatment and was ground up to less than 1 μm. The incorporation of more than 80% nano size palm oil fuel ash as cement replacement has produced a mortar having a compressive strength more than OPC mortar at a later age. The overall results have revealed that the inclusion of high volume nano palm oil fuel ash can produce a mortar mix with high strength, good quality and most importantly that is more sustainable.